Penerapan Ice Breaking Dalam Pembelajaran Bahasa Arab Untuk Meningkatkan Fokus Belajar Siswa SMP Swasta Pusaka - Khairunnisa Arfahmi; Zulfahmi Lubis (Departement of Mathematics Education, 2023)
Arabic lessons have been considered monotonous and seem less interesting. Therefore, the Ice Breaking method can be applied to attract students' interest and focus on learning Arabic. Ice Breaking is an activity that is carried out to attract the focus of attention and melt the teaching and learning atmosphere from its monotonous initial state to become more enthusiastic (active and conducive). The main capital of learning Arabic is being able to master Arabic vocabulary (mufrodat) well. As for this research using qualitative research with descriptive method. With research subjects namely the Principal, Arabic Teacher and Students. The technique of collecting data in this research is by observation, interviews and documentation. The results of this study are that the application of ice breaking can melt the learning atmosphere which was initially boring to become fun and can restore concentration and increase the enthusiasm of students to be more active in learning Arabic.